Principle of Common-ion Effect and its Application in Chemistry: a Review. - Peter AYOGU; Matthew Ezugwu; Fabian Eze (Journal of Chemistry Letters)
Common-ion effect is a shift in chemical equilibrium, which affects solubility of solutes in a reacting system. The phenomenon is an application of Le-Chatelier’s principle for equilibrium reactions that has become a regular occurrence in chemistry analysis and industrial researches. It is an important phenomenon that can be used in practice, to understand some reaction conditions that could favour an increased product formation. In Chemistry, its principle is thought to rely on its ability to exploit the availability of an ion present in each of the reacting compounds in a reacting system to suppress the solubility of one of the ionic substances upon contact with another ionic compound. Due to the precipitating effect of the presence of common-ions in equilibrium solutions, the common-ion effect is considered one of the factors that affect the solubility of a compound. The principle of common-ion effect applies in many chemical processes including those involved in buffering solutions, purification of salts, salting out of soap, precipitation of salts, manufacture of baking soda, water treatment and are frequently applied in many manufacturing industries including the pharmaceutical industries. In this paper, we performed a concise updated desk literature review on the principle of Common-ion effect with the view to provide a greater understanding of the concept and its importance in chemistry.